Spatial analysis of vitality indicators with emphasis on urban roads in Mashhad metropolis - Ahmad hajarian (اقتصاد شهری)
In recent decades, following the excessive expansion of cities and the increasing importance of automobiles, the role of urban streets in urban spaces has decreased, which has led to the creation of boring environments in cities and the reduction of the vitality of urban spaces. Therefore, the vitality of urban streets is one of the most important concerns of urban planners. The purpose of this research is to spatially analyze the vitality indicators with an emphasis on urban streets in the 13 regions of the Mashhad metropolis. The present research is of an applied type in terms of purpose and a descriptive-correlation study in terms of nature and method, and the data collection method is documentary (library) and field (questionnaire). SPSS and multi-criteria decision-making methods such as MEREC and COCOSO and the structural equation method (Smart PLS) have been used to analyze data and information. The study results show that regions 9, 1, and 4 have the highest, and regions 3, 12, and 10 have the lowest levels of vitality indicators with an emphasis on urban roads in Mashhad. Based on the results of the PLS structural equation testing, the leisure and recreation variable with a total impact coefficient of 0.658 has the greatest impact on vitality with an emphasis on urban roads. Then, the components of comfort and convenience (0.652), visual physical attractiveness and diversity (0.631), physical quality (0.623), safety and security (0.430), and accessibility (0.160) are effective on vitality with an emphasis on urban roads, respectively.